Radiation dose management in fluoroscopy procedures: less is more? - Siti Farizwana Mohd Ridzwan,; S. Elavarasi Selvarajah,; Hamzaini Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aims of this study are (1) to determine the scattered radiation dose levels in routine fluoroscopy procedures and (2) to compare them with the equivalent chest x-rays and also (3) to monitor common techniques and radiation safety measures taken by the medical officers. The study covered a sample of 105 fluoroscopic procedures performed by 18 medical officers. Each officer wore a personal pocket dosimeter inside the lead gown during each procedure. A digital dosimeter was placed near the detector of the fluoroscopy unit while a survey meter was positioned at the control panel area to record the dose levels. There were 14 types of examination included in this study. The total number of images captured was found to be the highest in barium swallow examination with 115 images, almost five times higher compared to the common practices. The longest screening time was observed in barium enema examination which is 9.15 seconds. The median of the scattered dose level was the highest in barium meal examination (165.50 μSv) which is equivalent to 8.28 times of average dose impart by chest x-ray examinations. The number of images and the length of screening time depend on the competency levels of the medical officers. They capture as many images as possible to avoid missing any abnormalities, therefore it will always be better if the fluoroscopist is consulted during each case. They should also consistently practice essential protection by minimizing exposure time, maximizing distance from the source tube and utilizing the radiation shielding.